Consumer protection in financial services – towards greater transparency with a key information document for packaged retail investment products - Kozłowska, Maja (University of Wroclaw. Faculty of Law, Administration & Economics, 2012)
Consumer protection in financial services – towards greater transparency with a Key Information Document for Packaged Retail Investment Products
Keywords: ochrona konsumentów; usługi finansowe